2014
DOI: 10.1371/journal.pone.0087023
|View full text |Cite
|
Sign up to set email alerts
|

Association between COX-2 rs 6681231 Genotype and Interleukin-6 in Periodontal Connective Tissue. A Pilot Study

Abstract: ObjectivesThe aim of this pilot study was to investigate associations between IL-6 and COX-2 expression in gingival biopsies and both clinical diagnosis and genotypes in the IL-6 and COX-2 genes.DesignA case-control study included 41 gingival biopsies obtained from Caucasian patients grouped according to clinical diagnosis of gingival health (n = 10), gingivitis (n = 15) or chronic periodontitis (n = 16). Immunohistochemistry analyses were performed to determine COX-2 expression in lamina propria, IL-6 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Currently, it is clearly documented that any dysregulation or imbalance of the gut microbiota might lead to changes in colocytes as well as extraintestinal disease (5,6). This disruption causes an extensive and persisting inflammatory reaction, manifested by up-regulation of an array of pro-inflammatory mediators both locally and systemically, such as; cyclooxygenase 2 (COX-2), prostaglandin E 2 (PGE 2 ), tumor necrosis factor α (TNF-α), nuclear factor kappa B (NFkB), and transforming growth factor β (TGFβ) among others (8)(9)(10). Persistent inflammatory reaction, in its turn, leads to the development of IBD by activating the Gut Associated Lymphoid Tissue (GALT) (4).…”
Section: Abstract One Of the Contributory Causes Of Colon Cancer Ismentioning
confidence: 99%
“…Currently, it is clearly documented that any dysregulation or imbalance of the gut microbiota might lead to changes in colocytes as well as extraintestinal disease (5,6). This disruption causes an extensive and persisting inflammatory reaction, manifested by up-regulation of an array of pro-inflammatory mediators both locally and systemically, such as; cyclooxygenase 2 (COX-2), prostaglandin E 2 (PGE 2 ), tumor necrosis factor α (TNF-α), nuclear factor kappa B (NFkB), and transforming growth factor β (TGFβ) among others (8)(9)(10). Persistent inflammatory reaction, in its turn, leads to the development of IBD by activating the Gut Associated Lymphoid Tissue (GALT) (4).…”
Section: Abstract One Of the Contributory Causes Of Colon Cancer Ismentioning
confidence: 99%
“…In recent study, it was shown that the CC COX2 rs6681231 genotype was not correlated with COX2 expression itself; however, in periodontal connective tissue, it was associated with the number of cells that are positive to IL-6. 44 The results of the present study suggest that that the CC genotype of the COX2 rs6681231 polymorphism is associated with an increased risk of GDM and the need for insulin therapy, whereas the TT genotype of the NOS3 rs1799983 polymorphism may be associated with the need for insulin therapy in women with GDM, although this hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 58%
“…have indicated that COX2 gene polymorphism is a risk factor for incident stroke in African Americans. In recent study, it was shown that the CC COX2 rs6681231 genotype was not correlated with COX2 expression itself; however, in periodontal connective tissue, it was associated with the number of cells that are positive to IL‐6 …”
Section: Discussionmentioning
confidence: 98%
“…Some studies demonstrated that polymorphisms of this gene can affect the concentration of IL-6 in serum (Erciyas et al, 2010;Mesa et al, 2014). Polymorphisms in promoter region of IL-6 gene affect transcription and expression of IL-6 in individuals.…”
Section: Il-6mentioning
confidence: 99%